2016
DOI: 10.2109/jcersj2.16109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of metal oxides with improved performance using a solvothermal method

Abstract: We have explored a solvothermal method for synthesizing various metal oxides in alcohol or glycol media at temperatures around 300°C. This review summarizes our recent results on the solvothermal synthesis of metal-oxide nanoparticles and their catalytic and photoluminescence performances. We have described the principles of solvothermal processing by classifying solvothermal methods according to the type of solvent used as follows: alcohol, vicinal glycol and 1,4-butanediol. (1) Solvothermal reaction of metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Several researchers have developed a solvothermal method to prepare WC powder. Solvothermal method is a synthetic method that uses organic or non-aqueous solvents as solvents to react the original mixture with the solution at a certain temperature under the spontaneous pressure in a closed system (Hosokawa, 2016).…”
Section: Liquid-phase Methodsmentioning
confidence: 99%
“…Several researchers have developed a solvothermal method to prepare WC powder. Solvothermal method is a synthetic method that uses organic or non-aqueous solvents as solvents to react the original mixture with the solution at a certain temperature under the spontaneous pressure in a closed system (Hosokawa, 2016).…”
Section: Liquid-phase Methodsmentioning
confidence: 99%
“…Solvothermal/hydrothermal synthesis typically demands lower sintering temperatures compared to solid-state methods, mitigating the risk of undesired phase formation and preserving scintillator purity [15,16]. Particularly well-suited for nanomaterial synthesis, these methods operate as a streamlined, single-step process, simplifying production and contributing to reduced environmental impact when compared to specific solid-state approaches [17,18]. Jin Young Park et al reported preparing the stable phase GGAG:Ce phosphors by this method, but the work was not successful [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, garnet-scintillating materials, such as Yttrium Aluminium Garnet (YAG) have been prepared via solvothermal synthesis, by using this method it can be possible to utilize organic solvents at temperatures above their boiling points , through which it can be possible that using high vapor pressure conditions increase the growth rate of solvothermal compare to the solid-state method [20][21][22]. The solvothermal method has several benefits for the preparation of micro/nanomaterials including size, shape, crystallinity, and particle high surface area [17,18]. Also in this method, the interaction of precursors during synthesis is facilitated by using a solvent at temperatures and pressures ranging from moderate to high.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of CeO2 nanoparticles and/or coatings can be achieved via different routes such as solvothermal [14], hydrothermal [15], precipitation [16][17][18] or thermal decomposition of complex precursors [19][20][21]. For the application of the latter technique, a good knowledge of the decomposition process is highly advantageous in order to control the morphology of the coating or nanoparticles as well as for ensuring safety during large scale handling due to the evolution of potentially toxic gases.…”
Section: Introductionmentioning
confidence: 99%